The absence of core piRNA biogenesis factors does not impact efficient transposon silencing in Drosophila. - Chary, S.; Hayashi, R. (PLoS Biology, 2023)
Organisms require mechanisms to distinguish self and non-self-RNA. This distinction is crucial to initiate the biogenesis of Piwi-interacting RNAs (piRNAs). In Drosophila ovaries, PIWI-guided slicing and the recognition of piRNA precursor transcripts by the DEAD-box RNA helicase Yb are the 2 known mechanisms to licence an RNA for piRNA biogenesis in the germline and the soma, respectively. Both the PIWI proteins and Yb are highly conserved across most Drosophila species and are thought to be essential to the piRNA pathway and for silencing transposons. However, we find that species closely related to Drosophila melanogaster have lost the yb gene, as well as the PIWI gene Ago3. We show that the precursor RNA is still selected in the absence of Yb to abundantly generate transposon antisense piRNAs in the soma. We further demonstrate that Drosophila eugracilis, which lacks Ago3, is completely devoid of ping-pong piRNAs and exclusively produces phased piRNAs in the absence of slicing. Thus, core piRNA pathway genes can be lost in evolution while still maintaining efficient transposon silencing.